Growing Birrul Walidainii Character in SMK Muhammadiyah Kramats as An Effort to Overcome Youth Distinctions - Hendri Hermawan Adinugraha; Mohammad Syaifuddin; Novendi Arkham Mubtadi (International Journal of Public Devotion, 2021)
The character building activity of “birrul walidainii” in students of SMK Muhammadiyah Kramat as an effort to overcome juvenile delinquency today is very much needed by society and teenagers today. Community service was carried out at SMK Muhammadiyah Kramat, Jl. Garuda No. 09, Kemantran, Kramat District, Tegal Regency, Central Java. The activity was carried out on Saturday, February 20, 2021. The target of this community service is Muhammadiyah Kramat Vocational High School Students, totaling 90 students. This community service partner is SMK Muhammadiyah Kramat. This community service activity method is carried out using the method of awareness / increasing understanding of the character “birrul walidainii” in SMK Muhammadiyah Kramat students as an effort to overcome juvenile delinquency. The implementation of a community service program which consists of several activities, namely awareness / increasing the importance of respect and obedience to parents, education on the urgency of the role of parents, and awareness / increasing the importance of respect and obedience to teachers. The factors that most play a role in causing delinquency in SMK Muhammadiyah Kramat students are family factors and environmental factors. Through awareness / increasing understanding of the character “birrul walidainii” in SMK Muhammadiyah Kramat students as an effort to overcome juvenile delinquency, parents and teachers of SMK Muhammadiyah Kramat have an important role in educating students of SMK Muhammadiyah Kramat. One way is to keep their children busy with general education and religious education, with the hope of fortifying students of SMK Muhammadiyah Kramat to avoid the influence of juvenile delinquency and so that parents, teachers, and students of SMK Muhammadiyah Kramat are able to establish two-way communication where Parents can immediately understand their role in educating children and children as well as students understand the meaning of “birrul walidaini”.